Moisture Sorption Characteristics with Net-Isosteric Heat Value of Maize Based Soy Protein Fortified Extruded Product - Chandrahas, Sahu; Shadanan , Patel; Dharmendra, Khokhar (Research Developments in Science and Technology Vol. 10, 2022)
Moisture sorption characteristics and net-isosteric heat of sorption are essential to know the storage stability, storage condition and selection of packaging materials. Sorption behavior of extruded product was studied at four different temperatures (30, 40, 50 and 60oC) under the relative humidity conditions of 11-92%. The product was developed from an optimized blend composition of maize, defatted soy, finger millet and yam in the proportion of 40:20:30:10 at an optimum condition of feed moisture 14% (WB), barrel temperature 110oC and screw speed 301 rpm. The sorption capacity of extruded product decreased with the increase in temperature at constant water activity. The equilibrium moisture content (EMC) was found to be increased with the increase in water activity (aw) at particular temperature. The highest EMC value (30.05%, db) was recorded at highest water activity (0.923 aw) and lower temperature (30oC), whereas the lowest EMC value (2.46%, db) at lowest aw (0.11) and higher temperature (60oC) condition. The isotherms exhibit curves of Type-II for all four experimental temperature conditions. The EMC data were fitted to six well known sorption models namely GAB, Smith, Oswin, Caurie, Iglesias & Chirife and BET to find best suitable model. The goodness of fit was evaluated on the basis of statistical parameters namely root mean square percentage error (%RMSE) and mean absolute percentage error (P). GAB model was found to be the best among them. The net isosteric heat of sorption of the extruded product was determined by using Clausius-Clapeyron equation. The net isosteric heat of sorption varied between 16.711 and 3.242 kJ/mol within 5-30% (db) of sample moisture content. The net-isosteric heat decreased with the increase in moisture content in the product.